Socio- political commentaries in Muazu Mohammed Sani’s paintings - Yahaya, Muhammad Sani; Waziri , Mohammadu Yahaya; Iyama,, Gordy (Technium Education and Humanities, 2025)
The concept of modern art in Nigeria was developed and sustained by the academically trained artists who were influenced by the socio- political and cultural experiences of their time. Prominent institutions like the Zaria Art School took up the challenge for a new direction after the country’s independence to commence the practice of “Natural Synthesis” as coined and abducted as the philosophy of the School. Similarly, the Uli experiment at the University of Nigeria, Nsukka and Ona at the Obafemi Awolowo University- Ife, immediately took off on a wider dimension. Subsequently, after many years of practice, the 1970s and 1980s sets of graduates of the Zaria Art School abandoned the “Natural Synthesis” idea for the new “universalist” approach influenced by the globalization process that reduces the world into a global village (Yahaya, 2010).